Study of Cervical Length in Bangladeshi Cadaver - Ara, Zubaida Gulshan; Islam, ASM Shafiqul; Zaman, Umme Kulsum Sharmin; Ara, Anjuman; Busreea, Reeva Aireen (Community Based Medical Journal, 2016)
This cross sectional descriptive study was done to see the length of the cervix in Bangladeshi cadaver to find out the anatomical variation and to compare it with other study findings. 60 post mortem specimens containing female genital organs particularly uterine cervix were collected by purposive sampling technique from cadavers of different age groups. All the collected specimens were fixed in 10% formalin solution. This study was carried out in the department of Anatomy, Mymensingh Medical College from July 2006 to June 2007. Both gross and fine dissections were performed to measure the length of the uterine cervix. We compare our study findings with that of the references. Maximum mean length of the cervix was found in the 13-45 years age group. It was 2.89 cm. CBMJ 2016 July: Vol. 05 No. 02 P: 26-28